Analisis Strategi Konservasi Ekowisata Mangrove Belawan Sicanang di Kecamatan Medan Belawan, Kota Medan - Meilinda Suriani Harefa; Restu Restu; Asnimar Duha; Anggi Violin Sinabutar; Edoy Nainggolan; Febbry Vebilola Manalu; Lisna Anggia Fortunata (Fakultas Teknik Universitas Cenderawasih, 2024)
The mangrove ecotourism area in Belawan Sicanang Village, Medan Belawan District, Medan City is one of the marine ecotourism-based areas which has mangrove forests as one of its tourist attractions. The aim of this research is to determine the potential and conservation strategies for the Belawan Sicanang mangrove ecosystem in Medan Belawan District, Medan City. The method used in this research is descriptive method. Data analysis in this research uses data analysis in the form of primary data, namely observations, interviews, secondary data, namely literature studies and data obtained from related agencies as well as SWOT (Strengths, Opportunities, Weakness, Threats) analysis. The results of this research show that the Sicanang Mangrove forest has great potential in supporting the sustainability of the coastal environment and the welfare of local communities as well as providing various ecological, economic, tourism and social benefits or potential for humans and the surrounding environment. The conservation strategy includes replanting and maintaining the mangrove forest.